Trichinella spiralis infection rapidly induces lung inflammatory response: the lung as the site of helminthocytotoxic activity - Gentilini, Maria Virginia (2011)
In the present work, we studied the kinetics of the appearance of different immunological parameters in the lungs during the intestinal phase of infection with Trichinella spiralis. We also evaluated the lung's role in the retention and death of this helminth in its migratory stage. To study these parameters, we used lung extracts, lung cell suspensions and rat lung tissue sections. During the intestinal phase of infection (days 0–13 post-infection, p.i.), an inflammatory response is elicited in the lungs, which reflects humoral, cellular and functional changes. These changes included an increased number of mast cells and eosinophils and the local production of IL-4, IL-5, IL-10, TNFα, IFNγ, IL-13, CCL11 and CCL28. We found hyperplasia of the bronchus-associated lymphoid tissue (BALT). Total and specific IgA, IgE, IgG1 and IgG2a were detected locally. The retention of the migratory larvae in the lung, together with the ex vivo cytotoxic capacity of the lung cells and antibodies present in the lung extracts, suggested that the lung was one of the immune defense organs against the pathogen's migration stage.